Simultaneous Appearance of Arteritic Anterior Ischemic Optic Neuropathy and Central Retinal Artery Occlusion in Giant Cell Arteritis - Ooi, Say Ting; Che Omar, Nor Anita; Yaakub, Azhany (Malaysian Journal of Medicine and Health Sciences, 2022)
Giant cell arteritis (GCA) is uncommon among Asian population. It is frequently associated with sight threatening complications. Simultaneous bilateral ocular involvement with different pathology is uncommon. We would like to highlight a rare case of GCA that was presented with transient visual loss over the right eye with simultaneous onset of central retinal artery occlusion as well as arteritic anterior ischemic optic neuropathy in both eyes. High dose intravenous methylprednisolone then subsequently maintenance dose of oral steroid and oral aspirin were given. His visual acuity remained the same after treatment. Early diagnosis and treatment of GCA is crucial. Visual outcome can be devastating if treatment is delayed.